Carnival, sexual violence and harm at Australian music festivals - Wadds, Phillip (The British journal of criminology, 2022)
Much has been written about the search for carnivalesque release in late-modern society, but relatively less attention has been paid to the harms experienced within this practice. Based on mixed-methods qualitative research including observational fieldwork at a large, multi-day camping festival in NSW, Australia, and in-depth interviews with victim-survivors of sexual violence occurring at Australian music festivals, this paper considers music festivals as sites of contemporary carnival. The paper examines the way in which situational, environmental and gendered dynamics shape these transgressive experiences. In doing so, it advances cultural criminological understandings of the carnivalesque by highlighting the bounded nature of carnival and the ‘cultural scaffolding’ that enables sexual violence and harassment at music festival events.